2016
DOI: 10.1007/s00228-016-2042-0
|View full text |Cite
|
Sign up to set email alerts
|

Medication use and drug-related problems among women at maternity wards—a cross-sectional study from two Norwegian hospitals

Abstract: Over four out of ten women in the maternity wards have DRPs, and many have questions about drug use during pregnancy and lactation. Many of the DRPs could probably be avoided by providing patient-reported treatment reviews to pregnant women as a part of antenatal care. Multidisciplinary collaboration including physicians, midwifes, and pharmacists in antenatal care and in maternity ward could possibly prevent DRPs and thereby promote patient safety for pregnant and lactating women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 42 publications
6
39
2
1
Order By: Relevance
“…The role of the pharmacists may be important, since they are often the first health care provider that pregnant women visit to request advice/information, in order to address misconceptions regarding the use of medications. This finding is in concordance with present literature [ 11 , 24 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…The role of the pharmacists may be important, since they are often the first health care provider that pregnant women visit to request advice/information, in order to address misconceptions regarding the use of medications. This finding is in concordance with present literature [ 11 , 24 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, studies in non-pregnant patients have shown the effectiveness of pharmacists' counselling on medication adherence, persistence, clinical management and therapeutic outcomes [16][17][18][19][20][21][22]. This is important since two recent studies have shown medication-related problems (MRP) frequently occur among pregnant women [23,24]. These MRP were largely resolved by pharmacists correcting misperceptions, providing information, and empowering the women to make safe decisions about medication use [23].…”
Section: Introductionmentioning
confidence: 99%
“…This is important since two recent studies have shown medication-related problems (MRP) frequently occur among pregnant women [23,24]. These MRP were largely resolved by pharmacists correcting misperceptions, providing information, and empowering the women to make safe decisions about medication use [23]. The potential contribution of pharmacists to improve fetal-maternal health has been recognized by the International Pharmaceutical Federation (FIP), stating that pharmacists can detect the use of potential teratogenic medicines and counsel pregnant women on alternative medicines [25].…”
Section: Introductionmentioning
confidence: 99%
“…A medication-related problem (MRP) is de ned as an unwanted event or circumstance involving medication therapy that actually or potentially interferes with desired health outcomes [1,2]. Studies have shown that the prevalence of MRPs among hospitalized pregnant patients varies from 42-83% [3,4].…”
Section: Introductionmentioning
confidence: 99%